Analysis of Corporate Financial Performance and Investment Opportunity Set On Company Value Comparative Analysis of Compass 100 and Lq45 Index Companies in Indonesia the Year 2017 – 2021 - Guntur Ramadan; Holiawati Holiawati; Nofryanti Nofryanti (Budapest International Research and Critics University, 2023)
The issue of Firm Value should be thoroughly investigated. Firm value is an essential indicator for investors in making investment decisions investing their funds in the company. The high corporate value will impact market confidence and prospects for the company. This study analyses Corporate Financial Performance and Investment Opportunities Set on Company Value. This research was conducted at Compass 100 and LQ45 companies, with a research sample of 170 and 90, respectively, for 2017-2021. To test the hypothesis of this study using the Fixed Effect method for the Compass 100 index and the Ordinary Least Squares (OLS) method for the LQ45 index. The results of this study indicate that the Compass 100 Investment Opportunity Set index affects firm value, but Corporate Financial Performance has no impact on firm value. In the LQ45 Investment Opportunity Set index, it affects company value, but Corporate Financial Performance does not affect company value. The LQ 45 index has better investment opportunities in the future than the Compass 100 index, meaning that the LQ 45 has a much higher growth opportunity. The company's value has always been a benchmark for the company's offering to investors; with good prospects for the company in the future, it will be a concern for investors; investors will observe the development of the company's value from time to time. When the company can maximize performance properly, the value of the company will be better.